2016
DOI: 10.1021/acs.est.5b04655
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Solubility Approach to Determine PDMS–Water Partition Constants and PDMS Activity Coefficients

Abstract: Freely dissolved aqueous concentration and chemical activity are important determinants of contaminant transport, fate, and toxic potential. Both parameters are commonly quantified using Solid Phase Micro-Extraction (SPME) based on a sorptive polymer such as polydimethylsiloxane (PDMS). This method requires the PDMS-water partition constants, KPDMSw, or activity coefficient to be known. For superhydrophobic contaminants (log KOW >6), application of existing methods to measure these parameters is challenging, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…Hung et al (2010) studied the discrepancy of partition coefficients in different studies and found that residual lipid in cell walls would sharply increase the partition coefficients of cell wall materials because of the high partition coefficients of PAHs in lipids. The root materials were ground into powders in previous studies (Hung et al 2010; Hale et al 2011; Szymanska‐Chargot et al 2015). Some of the ground root sorbents can dissolve out organic matter and as colloidal particles in water, which could increase the apparent solubility of PAHs (Grant et al 2016). Polycyclic aromatic hydrocarbons were dissolved into methanol in most past sorption experiments, and the influence of methanol concentration cannot be neglected.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hung et al (2010) studied the discrepancy of partition coefficients in different studies and found that residual lipid in cell walls would sharply increase the partition coefficients of cell wall materials because of the high partition coefficients of PAHs in lipids. The root materials were ground into powders in previous studies (Hung et al 2010; Hale et al 2011; Szymanska‐Chargot et al 2015). Some of the ground root sorbents can dissolve out organic matter and as colloidal particles in water, which could increase the apparent solubility of PAHs (Grant et al 2016). Polycyclic aromatic hydrocarbons were dissolved into methanol in most past sorption experiments, and the influence of methanol concentration cannot be neglected.…”
Section: Resultsmentioning
confidence: 99%
“…Partition coefficients are determined by equilibration of the materials with a water phase that contains the solutes of interest, followed by their concentration in the water phase and sorbents (Hung et al 2010). The sparing water solubility of HOCs can reduce the accuracy of analysis when determining the partition coefficients (Ma et al 2011; Grant et al 2016). Dissolved organic matter (DOM) and particles released from sorbents would influence the results of partition coefficients between water and sorbents (Wood et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To monitor for exceedance of thermodynamically based environmental quality criteria in the environment, various standard techniques can be used. Passive sampling techniques may provide a particularly simple and economically attractive method for monitoring if environmental quality objectives are met (Mayer et al ) because the concentrations of chemicals in samplers can be related to chemical activities in a highly reproducible manner (Grant et al ). The equilibrium partitioning approach (Di Toro et al ) has been used to develop sediment benchmarks for a range of organic chemicals (US Environmental Protection Agency ; Booij et al ).…”
Section: Theorymentioning
confidence: 99%